Synthesis of Colloidal Silicon Quantum Dot from Rice Husk Ash - Thu-Huong Le; Dang Thi Thanh Le; Nguyen Van Tung (Journal of Chemistry)
This article describes the synthesis procedure of colloidal silicon quantum dot (Si QDs) from rice husk ash. The silicon quantum dots were capped with 1-octadecene by thermal hydrosilylation under argon gas to obtain octadecyl-Si QDs (ODE-Si QDs). The size separation of ODE-Si QDs was examined by the column chromatography method, which used silica gel (40–63 μm) as the stationary phase. Finally, we obtained two fractions of silicon quantum dot, exhibiting blue emission (B-Si QDs) with an average size of 2.5 ± 0.73 nm and red emission (R-Si QDs) with an average size of 5.1 ± 0.68 nm under a UV lamp (365 nm). The PL spectra of B-Si QDs and R-Si QDs samples show maximum peak energy at 410 nm (3.02 eV) and 700 nm (1.77 eV), respectively, while the quantum yield of Si QDs decreases from 5.8 to 34.6% when the average size decreases from 2.5 nm to 5.1 nm. The above results of PL emission spectroscopy and UV-vis absorption show quantum confined effect in Si QDs.